1996
DOI: 10.1507/endocrj.43.241
|View full text |Cite
|
Sign up to set email alerts
|

Differential Changes of Corticotropin Releasing Hormone (CRH) Concentrations in Plasma and Synovial Fluids of Patients with Rheumatoid Arthritis (RA).

Abstract: Abstract.Corticotropin releasing hormone (CRH) and ACTH concentrations in plasma and CRH and IL-6 concentrations in synovial fluid in patients with rheumatoid arthritis (RA) were examined to clarify the relationship between cytokines and the hypothalamic-pituitary-adrenal axis (HPA axis).Concentrations of serum amyloid A protein (SAA), one of the acute phase proteins, were also measured as an indicator of inflammation. CRH and IL-6 concentrations in synovial fluid were higher in RA patients than in control pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Likewise, CRF was found to cause the release of cytokines such as IL-1, IL-2, and IL-6 from immune cells in vitro (Leu & Singh, 1992;Paez Pereda et al, 1995;Singh & Leu, 1990), to induce synthesis of acute phase proteins from liver hepatocytes (Hagan, Poole, & Bristow, 1993), and to stimulate the release of IL-1 from hypothalamic explants (Tringali et al, 1997). These ®ndings have culminated in the suggestion that CRF overproduction is involved in in¯ammatory disease states such as experimental uveitis (Mastorakos et al, 1995) and rheumatoid arthritis (Nishioka et al, 1996;Webster, Torpy, Elenkov, & Chrousos, 1998), which may be precipitated or exacerbated by exposure to stressors (e.g., Zautra et al, 1997). Because peripheral IL-1 can activate vagal afferents, which in turn can result in increased IL-1 in the brain (Hosoi, Okuma, & Nomura, 2000;Laye et al, 1995), there exists at least one empirically testable pathway by which peripheral CRF might, by means of stimulating peripheral cytokine activity, induce central cytokine activity such as is known to underlie sickness behaviors.…”
Section: Separation and Sickness Behaviormentioning
confidence: 97%
“…Likewise, CRF was found to cause the release of cytokines such as IL-1, IL-2, and IL-6 from immune cells in vitro (Leu & Singh, 1992;Paez Pereda et al, 1995;Singh & Leu, 1990), to induce synthesis of acute phase proteins from liver hepatocytes (Hagan, Poole, & Bristow, 1993), and to stimulate the release of IL-1 from hypothalamic explants (Tringali et al, 1997). These ®ndings have culminated in the suggestion that CRF overproduction is involved in in¯ammatory disease states such as experimental uveitis (Mastorakos et al, 1995) and rheumatoid arthritis (Nishioka et al, 1996;Webster, Torpy, Elenkov, & Chrousos, 1998), which may be precipitated or exacerbated by exposure to stressors (e.g., Zautra et al, 1997). Because peripheral IL-1 can activate vagal afferents, which in turn can result in increased IL-1 in the brain (Hosoi, Okuma, & Nomura, 2000;Laye et al, 1995), there exists at least one empirically testable pathway by which peripheral CRF might, by means of stimulating peripheral cytokine activity, induce central cytokine activity such as is known to underlie sickness behaviors.…”
Section: Separation and Sickness Behaviormentioning
confidence: 97%
“…In addition, during the process of inflammatory stress, various cytokines stimulate CRF secretion at local inflammatory sites, such as in the arthritic joint, but its action appears to be proinflammatory. Nishioka et al [37] reported that concentrations of CRF and interleukin-6 in synovial fluid were higher in RA patients than in OA patients, but that plasma corticotropin and CRF levels were significantly lower in RA patients than in OA patients. This may suggest that the secretion of CRF in synovial fluid is regulated differently from plasma CRF secretion, since CRF levels in the synovial fluid and plasma of RA patients showed opposite trends.…”
Section: Rt-pcr Of Urocortin and Crf-rs In Synovial Tissuementioning
confidence: 99%
“…This would culminate in inflammation and lowered pain threshold. 7 The CRH levels detected in the synovial fluid from RA patients, although lower than in osteoarthritis, 20 has the propensity to increase IL-6, 18 from macrophages and increase its activity after combining with CRHbinding protein, 21 and needs further research for its role in RA inflammation. …”
Section: Discussionmentioning
confidence: 99%